2013
DOI: 10.1016/j.mce.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the peroxiredoxin system by cytokines in insulin-producing RINm5F cells: Down-regulation of PRDX6 increases susceptibility of beta cells to oxidative stress

Abstract: Peroxiredoxins are a family of six antioxidant enzymes (PRDX1-6), and may be an alternative system for the pancreatic beta cells to cope with oxidative stress. This study investigated whether the main diabetogenic pro-inflammatory cytokines or the anti-inflammatory cytokine IL-4 modulate PRDXs levels and putative intracellular pathways important for this process in the insulin-producing RINm5F cells. RINm5F cells expressed significant amounts of PRDX1, PRDX3 and PRDX6 enzymes. Only PRDX6 was modulated by cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Finally, one recent study has revealed that pro-inflammatory cytokines reduced the expression of peroxiredoxin 6 in clonal b-cells, thereby rendering these cells more vulnerable to oxidative stress. 84 IL-4 reversed this effect. Taken together (and allowing for the fact that not all data are fully concordant) it can be argued that anti-inflammatory cytokines are likely to inhibit IL-1b induced NO production upstream of iNOS expression in b-cells; conceivably by modulation of NFkB activation.…”
Section: Impact Of Anti-inflammatory Cytokines On Islet Cell Viabilitmentioning
confidence: 86%
“…Finally, one recent study has revealed that pro-inflammatory cytokines reduced the expression of peroxiredoxin 6 in clonal b-cells, thereby rendering these cells more vulnerable to oxidative stress. 84 IL-4 reversed this effect. Taken together (and allowing for the fact that not all data are fully concordant) it can be argued that anti-inflammatory cytokines are likely to inhibit IL-1b induced NO production upstream of iNOS expression in b-cells; conceivably by modulation of NFkB activation.…”
Section: Impact Of Anti-inflammatory Cytokines On Islet Cell Viabilitmentioning
confidence: 86%
“…Similarly, a crosstalk between the Janus kinase (JAK)/STAT and NF‐κB pathways has been reported, showing that inflammatory cytokine signaling could impair IL‐6‐induced JAK/STAT activation (54). In addition, IL‐4, another anti‐inflammatory cytokine, which also signals via JAK/STAT, protects pancreatic β cells from the decrease in antioxidant enzyme peroxiredoxin 6, provoked by inflammatory cytokines (55). However, this issue still needs to be addressed for a better understanding of the cross‐talk among these cytokine signaling pathways in pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a main factor leading to diabetes and its associated complications (19). A recent study (42) in b-cells demonstrated that mRNA and protein expression of PRDX6 2/2 mice. Values are expressed as mean 6 SE.…”
Section: Discussionmentioning
confidence: 99%